Association of Optic Neuritis and Hipoparathyroidism - Mosquera Klinger, Gabriel Alonso; Pontificia Universidad Javeriana-Hospital Universitario San Ignacio (Pontificia Universidad Javeriana, 2013)
This article presents a case of a 70 year-old-man with a history of thyroid cancer, that during the previous year had undergone total thyroidectomy, and presented hypoparathyroidism as a post-surgical complication. The patient has 15 days of clinical symptoms of progressive loss of visual acuity in the right eye, also clinical and imaging findings compatible with right eye optic neuritis. During hospital stay, a diagnosis of optic neuritis was made and other common causes of optic neutiris in this age group were discarded.